Manajemen Pendidikan Inklusi di SDIT Harapan Bunda Purwokerto - Fatimah Azzahra; Ulpah Maspupah; Ahwat Fitriani; Nida Nur Akmalin; Intan Nurhayani; Salsatin Dian Saputri (Jurnal Kependidikan, 2026)
This study aims to provide an in-depth description of the inclusive education management implemented at SDIT Harapan Bunda Purwokerto, an Islamic elementary school that has been committed to accepting children with special needs and integrating them into one class with regular students since 2010. This study employed a qualitative approach, with data collection techniques including interviews, observation, and documentation. Then data analysis is carried out through the process of reduction, presentation, and drawing conclusions. Research shows that the implementation of inclusive education management at SDIT Harapan Bunda Purwokerto encompasses four main management functions: planning, organizing, implementing, and supervising. During the planning stage, the school develops an inclusive program each academic year, taking into account the previous year's evaluation, including the learning plan and the therapeutic needs of children with special needs. During the organizing stage, the school principal is assisted by an inclusion coordinator and a special assistant teacher to systematically implement the program. Learning is implemented flexibly, adapting learning materials based on the abilities of children with special needs. Supervision at the school is carried out periodically through administrative checks and monthly evaluations. This study also identified supporting and inhibiting factors that influence the program's success. These findings emphasize the importance of adaptive and collaborative management in implementing inclusive education in elementary schools.